2014
DOI: 10.1073/pnas.1321569111
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of genome activation in bovine embryos by RNA sequencing

Abstract: During maternal-to-embryonic transition control of embryonic development gradually switches from maternal RNAs and proteins stored in the oocyte to gene products generated after embryonic genome activation (EGA). Detailed insight into the onset of embryonic transcription is obscured by the presence of maternal transcripts. Using the bovine model system, we established by RNA sequencing a comprehensive catalogue of transcripts in germinal vesicle and metaphase II oocytes, and in embryos at the four-cell, eight-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
321
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(354 citation statements)
references
References 31 publications
26
321
3
4
Order By: Relevance
“…Notably, GOF activation occurred during the same period of preimplantation development as major embryonic gene activation in IVF embryos at the 8-cell stage. 3,17 Apparently major reprogramming of gene expression signified by GOF activation was correlated with structural changes of nuclei in cloned embryos, which were strikingly similar with structural changes observed in IVF embryos. 11 Cloned embryos approaching the 8-cell stage adopted Table 2.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Notably, GOF activation occurred during the same period of preimplantation development as major embryonic gene activation in IVF embryos at the 8-cell stage. 3,17 Apparently major reprogramming of gene expression signified by GOF activation was correlated with structural changes of nuclei in cloned embryos, which were strikingly similar with structural changes observed in IVF embryos. 11 Cloned embryos approaching the 8-cell stage adopted Table 2.…”
Section: Discussionsupporting
confidence: 64%
“…2 In bovine embryos major embryonic genome activation takes place at the 8-cell stage, where the largest proportion of genes becomes active during preimplantation development. 3 Some genes, however, are already activated earlier during minor genome activation. 4 The functional implications of nuclear architecture changes, which occur during this period, are currently not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcriptome analysis of the different developmental stages from oocyte to morula in both mouse and human reveal a sequential order of transcriptional changes in pathways of cell cycle, gene regulation, translation and metabolism, acting in a stepwise fashion from cleavage to morula [92]. In cattle, RNA sequencing analysis of transcripts in GV and M II oocytes, and in 4-, 8-, 16-cell and blastocyst stage embryos indicated that the largest proportion of gene activation was found in 8-cell embryos [93]. Cross-species comparisons between mouse and human showed that significant difference in developmental specificity and timing existed [92].…”
Section: Transcriptomics May Dissect the Detailed Gene Regulatory Mecmentioning
confidence: 99%